2019
DOI: 10.3390/su11247016
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Marketing Communication and Importance of Its Evaluation in an Online Environment

Abstract: Online marketing communication covers a wide area and thus promotes an extensive reach of advertising to a broad audience. Hotels can achieve certain goals through online communication, mainly an increase of hotel awareness; an improvement of their image; and an increase in the level of customer satisfaction and trust, or brand loyalty. Measurement of the effectiveness of communication tools in the online environment is still a challenge, whether in the academic world or in the business world, mainly due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 43 publications
0
35
0
9
Order By: Relevance
“…To evaluate the effectiveness of each marketing medium used, we must screen and select the best mix of cost-effective marketing tools. Those tools should reduce financial illiteracy and, at the same time, deliver a clear, consistent message through all possible communication channels [ 33 , 47 , 51 ]. Marketing communications tools should be focused on the following four components: first, establishing a comprehensive advertising campaign to promote a bank’s credibility, reputation and corporate image to SMEs; second, promoting new and modified products to be aligned with external conditions and internal business strategies; third, engaging in permanent public relations, regular interviews and media events, so as to inform SMEs of a bank’s regular activities; and finally, upscaling employees' skills and executive knowledge, as they leave the greatest impression on the SME perception of a bank’s financial products, services and their quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To evaluate the effectiveness of each marketing medium used, we must screen and select the best mix of cost-effective marketing tools. Those tools should reduce financial illiteracy and, at the same time, deliver a clear, consistent message through all possible communication channels [ 33 , 47 , 51 ]. Marketing communications tools should be focused on the following four components: first, establishing a comprehensive advertising campaign to promote a bank’s credibility, reputation and corporate image to SMEs; second, promoting new and modified products to be aligned with external conditions and internal business strategies; third, engaging in permanent public relations, regular interviews and media events, so as to inform SMEs of a bank’s regular activities; and finally, upscaling employees' skills and executive knowledge, as they leave the greatest impression on the SME perception of a bank’s financial products, services and their quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, each year the hotel industry is becoming increasingly marketable, bringing various elements of complexity into entrepreneurial operation and widening the areas of risk situations (Krizanova et al, 2019). Such areas as e-marketing and the use of social networks, ICT solutions as well as promoting destinations using films, literature and video games become increasingly important in the promotion of tourism destinations (Strielkowski, 2017;Katsoni, Dionysopoulou, 2018). Confusion and confusion occur in such a situation in achieving the hotels' final outcome, and therefore the extent of its risk increases.…”
Section: Institutional Aspects Of Risk Strategic Managementmentioning
confidence: 99%
“…In response, various researchers have demonstrated that a good relationship exists between an organization's CSR engagement and its economic performance [2][3][4] and social performance [5,6]. In this regard, the effectiveness of communication is a matter of great concern for all businesses in the recent era, because effective communication can improve the evaluation of an organization on the part of consumers [7]. Different scholars have acknowledged the importance of effective communication to induce consumers' identification with a brand [8,9].…”
Section: Introductionmentioning
confidence: 99%